2015
DOI: 10.1007/s13595-014-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ perceptions and preference profiles for wood surfaces tested with pairwise comparison in Germany

Abstract: Abstract& Key message Visual aspects of wood are appreciated in interior design and many other high-end applications. This study focuses on consumer preferences which are examined regarding visually different spruce floor samples. Results indicate specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 15 publications
(17 reference statements)
0
26
0
Order By: Relevance
“…It cannot be excluded that the pre-grouping of all floor samples into five pre-groups, out of which five samples were randomly selected, could have affected the results because not all respondents were assessing the same floor samples. As reported by Manuel et al (2015), a high differentiation into different VCs, can be substantially reduced based on consumers' similarity assessments. Pre-grouping, however, might be avoidable in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It cannot be excluded that the pre-grouping of all floor samples into five pre-groups, out of which five samples were randomly selected, could have affected the results because not all respondents were assessing the same floor samples. As reported by Manuel et al (2015), a high differentiation into different VCs, can be substantially reduced based on consumers' similarity assessments. Pre-grouping, however, might be avoidable in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A more expressed heterogeneity among the respondents might have resulted in less pronounced clustering results. The study of Manuel et al (2015) examined differences between consumers' preferences which turned out to be rather heterogenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have mainly focused on the psychological responses evoked by visual, haptic, and/or olfactory stimulation by wood using sensory evaluation methods [9][10][11][12][13][14][15][16]. A part of these studies was developed into the marketing research of wood products [17][18][19][20]. Some multi-modal studies have also been carried out [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no study has investigated the tactile preference of consumers in relation to raised grain. In the literature, studies that analysed the consumers' preferences of wood products were focussed on the visual characteristics of the surface like grain orientation, colouration and knot characteristics (Manuel et al 2015). Ramananantoandro et al (2013) showed that the wood density was a prime criterion when consumers chose a wood species for furniture.…”
Section: Introductionmentioning
confidence: 99%